EMOSI TOKOH NOVEL AKU LUPA BAHWA AKU PEREMPUAN KARYA IHSAN ABDUL QUDDUS - Sri Mulatsih, Wiwik (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2015)
The research was motivated by the phenomena that occur in the community, woman’s life who having a career with ambition and high ideals. With wishes and high expectations, but not all the desire and expectation is reached, thus eliciting emotions. Positive emotion who experienced by the main character was ecstatic, love, and pride/self confidence; Positive emotions is showed by Suad who became a member of Parliament, Chairman of the Organization of the women’s movement in Egypt, the presence of Suad desperately needed her husband, ability taking decision as well as being able to complete the task as a lecturer and a member of Parliament. Negative emotions who experienced by the main character is angry, sad, and guilt. Negative emotions are indicated when Suad anxious when her son dating, failing foster households, and feel lonely when left her child and husband, as well as educating her child failed. The emotion are expressed through the main charecrers make this novel has its own power to show the other side of women’s lives.